Associations between college/university campus characteristics and student body mass index - Caitlin P. Bailey; Angelo F. Elmi; Mary T. Hoban; Christine Kukich; Melissa A. Napolitano (Komiyama Printing Co. Ltd, 2022)
Background: Campus environments are associated with undergraduate weight. However, few studies have examined campus type and geographic location in relation to student weight. This article aimed to identify college/university students with elevated BMIs by campus type and region. Methods: Linear mixed effects regression models were fit to data from the American College Health Association-National College Health Assessment II. Analyses tested associations between campus type/region and student self-reported BMI. Results: The sample included 404,987 students from 445 schools with mean BMI 24.9 ± 5.8. Across all school types/regions, BMI confidence intervals included overweight values. Two-year and public school students had higher BMIs compared to four-year and private school students, respectively. Students in the Midwest had higher BMIs compared to students in the Northeast. In the South only, Minority Serving Institution (MSI) students had higher BMIs compared to non-MSI students. Conclusion: Healthy weight maintenance programs should be made available to undergraduate students.